THE CORRELATION OF SLEEP QUALITY AND SHORT-TERM MEMORY FUNCTION IN MEDICAL STUDENTS - Putu Emilia Dewi; I Made Oka Adnyana; Ketut Widyastuti; I Putu Eka Widyadharma (MNJ (Malang Neurology Journal), 2025)
Background: Study on the correlation of sleep quality with short-term memory function in medical students has a high urgency considering that intelligence and good memory function are essential for their performance and learning ability in the field. There are only a few related studies on medical students in the Faculty of Medicine and Health Sciences of Universitas Udayana. Objective: This study aims to determine the correlation between sleep quality and short-term memory function of medical students in the Faculty of Medicine and Health Sciences of Universitas Udayana. Methods: The sample was determined by the non-probability consecutive sampling method. The Indonesian version of the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the Digit Span Backwards Task assessed sleep quality and short-term memory function respectively. The data was analyzed by Pearson correlative test and logistic regression multivariate analysis. Results: There were 75 subjects in this study. The PSQI average score of the respondents was 9.35 ± 4.45, and the Digit Span Backwards Task average was 3.75 ± 1.77. The Pearson correlative test showed a moderate correlation between sleep quality and short-term memory function (r = -0.44.; p < 0,05). The logistic regression multivariate analysis found that sleep disturbances affect short-term memory function more than other sleep quality components, with a probability value of 98%. Conclusion: There is a correlation between sleep quality and short-term memory function of medical students in the Faculty of Medicine and Health Sciences of Universitas Udayana.